Ultrasound Features Associated With Shoulder Complaints: Calcifications Larger Than 6 mm in Young Patients and Positive Doppler Are Associated With Pain - Janeiro, João; Barreira, Sofia C.; Martins, Patrícia; Ninitas, Pedro; Campos, Jorge; Fonseca, João E. (Frontiers in Medicine, 2021)
Objectives: To identify ultrasound features associated with the presence of shoulder complaints. Methods: This observational, case-control study, compared ultrasound findings between participants with and without shoulder complaints, matched for age, sex and dominancy. Data was collected from February 2018 to June 2020. Two-tailed Fisher's and Mann-Whitney U tests were used, with p values < .05 considered significant. Results: A total of 202 participants were enrolled (median age 56 years, range 18 to 70, 155 women), comprising 140 cases and 62 controls. A calcification size >= 6 mm, when age < 56 (p = .02), and a distance to tendon insertion >= 6 mm, when age >= 56 (p = .009), were only found in symptomatic shoulders. Color Doppler in rotator cuff tendons predominated in the presence of symptoms (26/140 vs 2/62, p = .003). An algorithm also combining the number of calcifications, tendon echotexture and insertional thickening, osseous irregularity, cuff tears and subacromial effusion showed a 92% (57/62) specificity for shoulder pain on this study sample. Conclusion: Calcification diameter of 6 mm or more is associated with shoulder pain in patients younger than 56 years. A distance from calcification to tendon insertion of 6 mm or more is related to pain in older patients. Doppler signal also is associated with shoulder pain. An algorithm based on a set of specific ultrasonographic criteria have a strong association with the presence of symptoms.